ANALISIS PENJUALAN ALAT-ALAT KB SECARA BEBAS MENURUT FIQIH MUAMALAH (Studi Kasus Apotek Di Kota Batusangkar) - Fauziah Fauziah; Hidayati Fitri (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The problem in this research is that if you look at the pharmacies around Batusangkar City, The contraception is traded freely without special supervision and is very much abused by the community which will result in harm to the community, many young people are currently having husband and wife relations without any marriage bond, this is caused by the existence of supporting facilities which are very easy to obtain and are sold freely. In this case, the question arises how the contraception can be bought and sold freely without special supervision and what is the view of Fiqh Muamalah on the buying and selling of the contraception like this. The type of research used is field research with a qualitative descriptive approach. The data sources in this study are primary data sources and secondary data sources, in which the primary data sources are Pharmacy Employees, consumers who have made buying and selling transactions for family planning equipment and the Investment and One-Stop Services Office of Tanah Datar Regency. Meanwhile, secondary data sources are obtained by conducting literature studies such as scientific books, research results, and journals on laws and BKKBN Regulations of the Republic of Indonesia. Data collection techniques used in this study were interviews and documentation. Data analysis techniques, namely the stages of data collection, data reduction, data presentation, and drawing conclusions. The type of triangulation that the authors use in this study is source triangulation. The results of the study can be concluded that the system for selling family planning devices in Batusangkar City is carried out freely without any special terms and conditions from the Pharmacy, this is not in accordance with positive law in Indonesia contained in the BKKBN Regulation of the Republic of Indonesia Number 9 of 2019 According to Fiqh Muamalah, the sale of family planning devices at the Batusangkar City Pharmacy is permissible as long as they meet the terms of sale and purchase, the pillars of sale and purchase and their use, but if the family planning devices are used for immorality or committing adultery then this transaction is prohibited or forbidden.